Effect of Yucca schidigera and Natural Zeolite on Broiler Performance - Cabuk, M.; Alcicek, A.; Bozkurt, M.; Akkan, S. (International Journal of Poultry Science, 2004)
The effects of dietary supplementation of Yucca schidigera and natural zeolite on broiler performance, ammonia concentration of broiler house, litter moisture, fecal dry matter and fecal crude ash were investigated. One day-old, nine hundred and sixty unsexed broiler chicks obtained from a commercial hatchery were divided into 4 treatment groups of 240 birds each. Birds were randomly assigned to the four treatment diets, consist of control, 15 g natural zeolite/kg, 25 g natural zeolite/kg and 120 mg Yucca schidigera/kg. Body weights of birds were significantly (P<0.05) different among the treatments, birds fed on diet containing 120 mg Yucca schidigera /kg being the highest and this treatment was followed by chicks fed diet control at days 21 to 42 and 42nd day. Feed conversion ratio was not affected by the supplementation of Yucca schidigera and natural zeolite at days 21 to 42. From 21 to 42 and 42nd day of age, the feed intake was not significantly different between the treatments. Ammonia concentration of house was significantly (P<0.05) decreased by adding Yucca schidigera and natural zeolite to diet. The supplementation of Yucca schidigera and natural zeolite to the diet reduced significantly (P<0.01) fecal dry matter and crude ash. On the other hand, dry matter of the broiler litter and livability were not affected by treatments. It can be concluded that the supplementation of Yucca schidigera to the diet reduced ammonia concentration in broiler house, fecal dry matter and crude ash without any adverse effect of broiler performance.